Analytic and Continental Philosophy: Methods and Perspectives. Proceedings of the 37th International Wittgenstein Symposium - Rinofner-Kreidl, Sonja; Wiltsche, Harald A. (De Gruyter, 2016)
Metaphilosophy; Analytic philosophy; continental philosophy